Peran Media Sosial dalam Mengawal Isu Lingkungan Hidup : (Studi Netnografi pada Akun Instagram @pandemictalks - Amalia Rizky Fatonah (Jurnalistik dan Media, 2023)
In recent times, Indonesia has been shocked by environmental issues related to air pollution. Excitement was reported on various social media related to the poor air quality that hit several cities in Indonesia. Environmentally-focused activists are beginning to take up their role on social media. One of them is @pandemictalks's Instagram account, which since the pandemic has been considered a vocal account related to environmental issues. This study aims to illustrate the role of @pandemictalks Instagram account related to the issue of air pollution in Indonesia. The research method carried out is a qualitative descriptive approach with Netnographic methodology. The results showed that @pandemictalks account is very aware and invites the public to care about the issue of air pollution.